Olfactory Proteins and Their Expression Profiles in the Eucalyptus Pest Endoclita signifier Larvae - Zhang, Xiaoyu; Yang, Zhende; Yang, Xiuhao; Ma, Hongxuan; Liu, Xiumei; Hu, Ping (Frontiers in Physiology, 2021)
Endoclita signifier Walker (Lepidoptera: Hepialidae), a polyphagous insect, has become a new wood-boring pest in Eucalyptus plantations in southern China since 2007, which represents a typical example of native insect adaptation to an exotic host. After the third instar, larvae move from soil to standing trees and damage the plants with a wormhole. Although females disperse to lay eggs, larvae can accurately find eucalyptus in a mingled forest of eight species, which leads us to hypothesize that the larval olfactory system contributes to its host selection. Herein, we investigated the transcriptomes of the head and tegument of E. signifer larvae and explored the expression profiles of olfactory proteins. We identified 15 odorant-binding proteins (OBPs), including seven general OBPs (GOPBs), six chemosensory proteins (CSPs), two odorant receptors (ORs), one gustatory receptor (GR), 14 ionotropic receptors (IRs), and one sensory neuron membrane protein (SNMP). Expression profiles indicated that all olfactory proteins, except for EsigCSP1, were expressed in the head, and most were also detected in non-olfactory tissues, especially thorax tegument. Furthermore, EsigOBP2, EsigOBP8, EsigGOBP1, EsigGOBP2, EsigGOBP5, EsigCSP3, EsigCSP5, and EsigOR1 were expressed most strongly in the head; moreover, EsigCSP3 expressed abundantly in the head. EsigGR1 exhibited the highest expression among all tissues. Besides phylogenetic analysis shows that EsigGOBP7 probably is the pheromone-binding protein (PBP) of E. signifier. This study provides the molecular basis for future study of chemosensation in E. signifier larvae. EsigCSP3 and EsigGR1, which have unique expression patterns, might be factors that govern the host choice of larvae and worth further exploration.